Debunking stereotypes: librarian character representation in the anime world - Nurpratama, Muhammad Rifky (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The purpose of this research is to examine the representation of librarian characters in anime according to Stuart Hall's model of representation. Information utilized within the current study is derived from the article